Automata - Laviña, Charlemagne Garcia; Niguidula, Jasmin De Castro (Manila, Philippines : Mindshapers Co. Inc., 2010)
The major objective of automata is to develop methods by which computer scientists can describe and analyze the dynamic behavior of discrete systems, in which signals are sampled periodically. The behavior of these discrete systems is determined by the way the system is constructed from storage and combinational elements. This book, Automata Theory will deal with the theoretical branch of Computer Science in terms of mathematical theory and simple class of algorithms. The abstract model of machines called automators will show simulation of machine computations through series of states and configurations.
Chapter 1: Sets -- Chapter 2: Languages -- Chapter 3: Regular Expressions and Context Free Grammars -- Chapter 4: Finite Automata -- Chapter 5: Finite Automata with Output -- Chapter 6: Pushdown Automata.
Includes bibliographical references.
Keywords: MACHINE THEORY